Pengaruh Kepemimpinan, Komunikasi, Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Telkomsel Region Kalimantan - Dzaky Firdaus Sarujih, Muhammad; Hadiyatno, Didik; Yuliani, Tutik (Jurnal GeoEkonomi, 2026)
This study aims to examine and analyze the influence of leadership, communication, and work environment on job satisfaction of Telkomsel Kalimantan Region employees. This study uses a quantitative approach. The sampling technique uses purposive sampling technique with permanent employee criteria with a sample of 115 respondents. Data collection methods are carried out through interviews, documentation, and questionnaire distribution. Data analysis uses SmartPLS software. The results of the study indicate that: leadership and work environment influence job satisfaction of Telkomsel Kalimantan Region employees and communication does not influence job satisfaction of Telkomsel Kalimantan Region employees